A new species of Tradescantia (Commelinaceae) from the state of Queretaro, Mexico - Zamudio, Sergio; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Ceja-Romero, Jacqueline (Instituto de Ecología, A.C., 2013)
Tradescantia murilloae Zamudio, Espejo, López-Ferrari et Ceja, a new species from Querétaro, Mexico is described and illustrated. The new taxon is compared with T. crassifoliaCav., a species with similar characteristics from which differs by the presence of a conspicuous rhizome, smaller leaves and flowers and different substrate and vegetation type in which it grows.